Transformasi pembelajaran Pendidikan Agama Islam melalui media digital di Sekolah Menengah Kejuruan - Verawati, Fauziah; Mustofa, Triono Ali (Program Studi Magister Pendidikan Agama Islam, 2026)
Advancements in digital technology have driven significant changes in school education methods, including the subject of Islamic Religious Education (Pendidikan Agama Islam or PAI) at the Vocational High School (Sekolah Menengah Kejuruan or SMK) level. The characteristics of the student body, which is dominated by Generation Z and Generation Alpha, necessitate innovative learning methods that are adaptive to technological developments. The objective of this study is to investigate the transformation of PAI learning methods resulting from the utilization of digital media at SMK Batik 2 Surakarta, specifically focusing on the improvement of student engagement, material comprehension, and learning efficiency. In this study, a qualitative method was employed to collect data through interviews with PAI teachers. The data were analyzed descriptively through the processes of reduction, display, and conclusion drawing. The results indicate that the use of digital media such as visual presentations, instructional videos, audio-visual media, and digital-based educational games enhanced student response and engagement in PAI learning. Digital media proved effective in assisting students in understanding abstract PAI concepts, particularly regarding aspects of Aqidah (creed), Akhlak (morals/ethics), and Islamic history. Although the implementation of digital media continues to face technical constraints regarding facilities and infrastructure, PAI teachers have undertaken various efforts to ensure that learning remains effective. This study concludes that the utilization of digital media is capable of improving the quality of PAI learning at SMK Batik 2 Surakarta and requires support through adequate facilities as well as the continuous improvement of teacher competence. Abstrak Kemajuan teknologi digital telah mendorong perubahan besar dalam metode pendidikan sekolah, termasuk mata pelajaran Pendidikan Agama Islam (PAI) di jenjang sekolah menengah kejuruan. Karakteristik peserta didik yang didominasi oleh generasi Z dan generasi Alfa menuntut adanya inovasi metode pembelajaran yang adaptif terhadap perkembangan teknologi. Tujuan dari penelitian ini adalah untuk menyelidiki perubahan metode pembelajaran PAI yang dihasilkan dari penggunaan media digital di SMK Batik 2 Surakarta, khususnya dengan fokus pada peningkatan keaktifan siswa, pemahaman materi, dan efisiensi pembelajaran. Dalam penelitian ini, metode kualitatif digunakan untuk mengumpulkan data dengan melakukan wawancara dengan guru PAI. Data dianalisis secara deskriptif melalui proses reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penggunaan media digital, seperti presentasi visual, video pembelajaran, media audio-visual, dan permainan edukatif berbasis digital, meningkatkan respons dan keterlibatan siswa dalam pembelajaran PAI. Media digital terbukti membantu siswa dalam memahami materi PAI yang bersifat abstrak, terutama pada aspek akidah, akhlak, dan kisah-kisah keislaman. Meskipun implementasi media digital masih menghadapi kendala teknis terkait sarana dan prasarana, guru PAI melakukan berbagai upaya untuk memastikan pembelajaran tetap berjalan efektif. Penelitian ini menyimpulkan bahwa pemanfaatan media digital mampu meningkatkan kualitas pembelajaran PAI di SMK Batik 2 Surakarta dan perlu didukung dengan fasilitas yang memadai serta peningkatan kompetensi guru secara berkelanjutan.